ANALYSIS OF THE PRODUCTIVITY OF AQUACULTURE BUSINESS IN FLOATING NET KARAMBA IN CIRATA RESERVOIR (CASE STUDY OF MARGALAKSANA VILLAGE, CIPEUNDEUY DISTRICT) - Millatina, Nabilah Sani; Suryana, Asep Agus Handaka; Andriani, Yuli; Maulina, Ine (Universitas Mataram, 2025)
Productivity is a concept that describes the relationship between output (production results) and input used (land area, seeds, feed) as one of the efforts that can be made to encourage growth and development in the fisheries and marine sectors. This study aims to analyze the level of productivity and factors that influence the productivity of fisheries cultivation efforts in Floating Net Cage (KJA) in Cirata Reservoir, West Bandung Regency. This study uses a case study method with a sampling technique using the purposive sampling method. The data collection technique is assisted by observation and interview methods with questionnaires, then the data obtained is analyzed using a quantitative descriptive approach. The results of the study showed that the level of productivity per unit area was 14.683 kg/yr/m2 and productivity per unit cost was IDR 19.016/kg. The Financial Analysis carried out produced a profitable R/C ratio value of 1,17. Factors that significantly affect cultivation productivity include land area, seed quality, feed conversion, and length of experience, while the age variable did not show a significant effect on productivity.